A Study of Propensity Factors Leading to the Runaway in Girls (Medical Forum Monthly, 2024)
Objective: The study was conducted to identify the causes and features of women for seeking shelter at Dar-ul-Aman located in Quetta city.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at Department of Behavioral Sciences and Community Medicine Quetta Institute of Medical Sciences (QIMS), Quetta Cantt from July 2015 to December 2015.Materials and Methods: The sample of 20 girls was taken from Dar-ul-Aman and interview schedule was administered, to assess the cause of the various variables was taken along with the case histories.Results: After collection of the data the results were analyzed in the light of the objective to the study. It can said that conflict in family, unhealthy influence of mass media, marriage problem bettering wife or abusive husband are the factors or reasons leading to runaway.Conclusion: Sample can be collected from different Dar-ul-Aman and should not only collected from Dar-ul-Aman but also from various other places such as polices stations film studious, red light areas and from those houses where such girls reach. To get more reliable result. It may be suggested that sample should be large enough to get more valid results.